2016
DOI: 10.1089/scd.2015.0299
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Remodeling in Chicken Induced Pluripotent Stem-Like Cells

Abstract: Chicken pluripotent stem cells (PSCs), such as embryonic stem cells and blastoderm cells, have been used to study development and differentiation in chicken. However, chicken PSCs are not widely used because they are hard to maintain in long-term culture. Recent reports suggest that chicken somatic cells can be reprogrammed to pluripotent state by defined factors to form induced pluripotent stem cells (iPSCs). These chicken iPSCs showed pluripotent differentiation potential and could be maintained in long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Choi et al, in 2016, shed light on the structural changes that occur within chicken cells during the process of reprogramming, providing insights into the cellular mechanisms involved in iPSC generation and pluripotency acquisition. Through electron microscopy, it was observed that intracytoplasmic organelles in differentiated somatic cells underwent remodeling during cell reprogramming and that ciPSCs exhibited a higher nucleus-tocytoplasm ratio and contained globular mitochondria with immature cristae [111].…”
Section: A Brief History Of Avian Ipsc Productionmentioning
confidence: 99%
“…Choi et al, in 2016, shed light on the structural changes that occur within chicken cells during the process of reprogramming, providing insights into the cellular mechanisms involved in iPSC generation and pluripotency acquisition. Through electron microscopy, it was observed that intracytoplasmic organelles in differentiated somatic cells underwent remodeling during cell reprogramming and that ciPSCs exhibited a higher nucleus-tocytoplasm ratio and contained globular mitochondria with immature cristae [111].…”
Section: A Brief History Of Avian Ipsc Productionmentioning
confidence: 99%
“…The discovery of chick ESCs and blastodermal cell culture emphasizes the conserved network regulating pluripotency required at least leukemia inhibitory factor (LIF) ( Etches et al, 1997 ; Pain et al, 1996 ), a cytokine used to culture naïve mouse ESCs and iPSCs ( Niwa et al, 1998 ; Takahashi and Yamanaka, 2006 ). In addition, basic fibroblast growth factor (bFGF), a cytokine used to cultivate primed human ESCs/iPSCs ( Thomson et al, 1998 ; Takahashi et al, 2007 ), is required in several avian ESCs/iPSCs studies ( Pain et al, 1996 ; van de Lavoir et al, 2006 ; Whyte et al, 2015 ; Choi et al, 2016 ; Katayama et al, 2018 ). Thus, this suggests that pluripotent stem cells from avian species exhibit some bias in a naïve-primed direction which could depend on other culture supplements.…”
Section: In Vitro Culture: Essential Toolkit For Avian Pluri...mentioning
confidence: 99%
“…Somatic cell reprogramming appears to be far more difficult to achieve in non-mammalian species. Few studies, using human and mouse transcription factors as reprogramming genes reported the derivation and characterization of iPS-like cells in chicken (designated ciPS cells) (Choi et al, 2016;Yu et al, 2014;Lu et al, 2015;Rosselo et al, 2013). By using chicken genes, iPS-like cells were also generated.…”
Section: Re-capturing Avian Pluripotency In Vitromentioning
confidence: 99%